Comparative Histopathological Study of Ciprofloxacin Impact on Mus Musculus Renal Cortex Infected with Multi-drug Resistance and Susceptible Uropathogenic Escherichia Coli - Al-Zaidi, Omar; Estabraq A. Mahmoud; Luma Abdulhady Zwain (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2026)
Urinary tract infections are mainly caused by uropathogenic Escherichia coli, which represent a significant global issue along with the rising of antibiotic resistance and treatment challenges. The aim of this study was to evaluate ciprofloxacin efficacy as a treatment in animal models following infection with multidrug-resistant UPEC and multidrug-susceptible UPEC and to determine the nephrotoxic effect of these antibiotics on the renal cortex. Up to 76 E. coli isolates were collected from UTI patients in Baghdad province, characterized by morphological and biochemical features, and confirmed using the Vitek-2 compact system. Mice were orally infected via gastric gavage with G33 using a bacterial load of 107 cells/ml, followed by post-infection treatment strategies with the aid of ciprofloxacin post-infection. Efficacy was determined by reduction in bacterial load, body weight, and renal cortex cross-sections. Ciprofloxacin significantly reduced the bacterial load but also caused toxicity to the kidney, such as tubular necrosis, hemorrhage, and congestion of glomeruli. This study highlights the urgent need for specialized antibiotic treatment systems to reduce drug resistance and nephrotoxicity effects. Further studies are essential to minimize renal damage.